Advertisement
Advertisement
Last updated at Feb. 12, 2020 by Teachoo
Transcript
Ex 3.3, 22 Prove that cot ๐ฅ cot 2๐ฅ โ cot 2๐ฅ cot 3๐ฅ โ cot 3๐ฅ cot ๐ฅ = 1 Taking L.H.S. cot x cot 2x โ cot 2x cot 3x โ cot 3x cot x = cot x cot 2x โ cot 3x (cot 2x + cot x) = cot x cot 2x โ cot (2x + x) (cot 2x + cot x) = cot x cot 2x โ ((cot 2x cot x โ 1)/(cot x + cot 2x)) (cot 2x + cot x) = cot x cot 2x โ (cot 2x cot x โ 1) = cot x cot 2x โ cot 2x cot x + 1 = 1 = R.H.S. Hence L.H.S = R.H.S Hence proved
(x + y) formula
About the Author